PENGARUH KESADARAN HALAL DAN SERTIFIKAT HALAL TERHADAP MINAT BELI PRODUK COKELAT CADBURY PADA MAHASISWA KAMPUS INSTITUT STIAMI JAKARTA - Irfan Wahyu Kurniawan; Abbas Mansyur; Supriyono Supriyono (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to analyze how much influence halal awareness and halal certification have on the interest in buying cadbury chocolate products for STIAMI Institute campus students in Jakarta.This study uses a quantitative approach with an associative type and with primary data as a source of data obtained from the results of the questionsnaire. The populattion were Muslim students’ of the 2015 business administration who attended the STIAMI Institute campus in Jakarta. The sample used was 137 respondents using purposive sampling method. Data analysis methods in this study are vidity and realibility test, normality test, correlation coefficient analysis, multiple linear regression analysis, test coefficient of determination and hypothesis testing.The results of the study found that: (1) Halal awareness had a positive effect on buying interst with a regression value 0f 0.273 and a significance level of 0,000. (2) Halal certification has a positive effect on buying interest with a regression value of 0.406 and a significance level of 0,000. (3) Halal awareness and Halal certification simultaneously have a positive effect on buying interest with a calculated F value of 131.935 greater than F table of 3.06 and a significance level of 0.000 less than 0.05. (4) The influence amount of Halal Certification on buying interest is 66.3% while the remaining 33.7% is influenced by other variablels not examined by the author.